Cage-like Ta@Bqn complexes (n = 23–28, q = −1–+ 3) in 18-electron configurations with the highest coordination number of twenty-eight. Issue 16 (11th April 2018) - Li, Hai-Ru; Liu, Hui; Lu, Xiao-Qin; Zan, Wen-Yan; Tian, Xin-Xin; Lu, Hai-Gang; Wu, Yan-Bo; Mu, Yue-Wen; Li, Si-Dian
Abstract : First-principles investigations predict the possibility of endohedral cage-like Ta@B q n complexes ( n = 23–28, q = −1–+ 3) in 18-electron configurations with the highest coordination number of twenty-eight in spherical environments. Abstract : Inspired by recent observations of the highest coordination numbers of CN = 10 in planar wheel-type complexes in D 10h Ta@B10 − and CN = 20 in double-ring tubular species in D 10d Ta@B20 − and theoretical prediction of the smallest endohedral metalloborospherene D 2 Ta@B22 − (1 ) with CN = 22, we present herein the possibility of larger endohedral metalloborospherenes C 2 Ta@B23 (2 ), C 2 Ta@B24 + (3 ), C 2v Ta@B24 − (4 ), C 1 Ta@B25 (5 ), D 2d Ta@B26 + (6 ), C 2 Ta@B27 2+ (7 ), and C 2 Ta@B28 3+ (8 ) based on extensive first-principles theory investigations. These cage-like Ta@B q n complexes with B6 pentagonal or B7 hexagonal pyramids on their surface turn out to be the global minima of the systems with CN = 23, 24, 24, 25, 26, 27, and 28, respectively, unveiling the highest coordination number of CN = 28 in spherical environments known in chemistry. Detailed bonding analyses show that1–8 as superatoms conform to the 18-electron configuration with a universal σ + π double delocalization bonding pattern. They are effectively stabilized via spd–π coordination interactions between the Ta center and η n –B n ligand which match both geometrically and electronically. Such complexes may serve as embryos of novel metal–boride nanomaterials.